Agronomic Effectiveness of Biochar–KCl Composites for Corn Cultivation in Tropical Soils - Gabrielly Nayara Tavares Silva Rodrigues; Carlos Alberto Silva; Everton Geraldo de Morais (Soil Systems)
Potassium chloride (KCl) is the main source of potassium (K) in Brazilian agriculture, but its high import dependency and the need for split applications increase costs and expose the system to supply and efficiency risks. Understanding the availability and release kinetics of potassium (K) from biochar-based fertilizers (K-BBFs) is crucial for optimizing their use as full or partial substitutes for KCl in Brazilian agriculture. This study evaluated biochars derived from banana peel (BP), coffee husk (CH), and chicken manure (CM), both in their pure form and co-pyrolyzed with KCl (composites) at 300 °C and 650 °C, as K sources for corn grown in two contrasting Oxisols. For pure biochars, feedstock type and pyrolysis temperature significantly influenced K content and release kinetics. Higher pyrolysis temperatures increased K content in BP and CH biochars but not in CM, while also slowing K release in CH and CM. Co-pyrolysis with KCl increased biochar yield, ash content, and K availability. Composites released more K than pure biochar but less than KCl, and at a slower rate. Notably, banana peel biochar co-pyrolyzed with KCl at 650 °C (CBP650) exhibited 36% slower K release and reduced KCl use by 82% while maintaining similar K use efficiency and corn growth. All K-BBFs matched KCl in promoting robust corn growth in clay soil, increasing biomass by 5.3 times and K uptake by 9 times compared to unfertilized (no K addition) plants. In sandy Oxisol, K-BBFs boosted biomass by up to 3.5 times compared to unfertilized plants, though some pure biochars were less effective than KCl in supporting full corn growth. Soil texture strongly influenced K availability, with sandier soils exhibiting higher K levels in solution. These findings suggest that kinetic release studies in abiotic systems, such as lysimeters with sand, are not suitable for evaluating K-BBFs as slow-release fertilizers. Due to lower K retention in sandy soil and solution K levels exceeding 1100 mg L−1, split applications of some K-BBFs are recommended to prevent corn cation uptake imbalances and soil K leaching. Additionally, granulating biochar–KCl composites may enhance K retention and regulate its release in sandy Oxisols.